Relationship between adverse drug reactions to antibacterial agents and the Klebsiella pneumoniae carbapenemase-producing (KPC) Klebsiella pneumoniae outbreak: insight from a pharmacovigilance study - Milo Gatti; Emanuel Raschi; Fabrizio De Ponti (BMC, 2019)
Abstract Background The management of Klebsiella pneumoniae carbapenemase producing (KPC) infections represents a major challenge. Several safety and efficacy concerns are shared by available antibiotics used in KPC infections, leading to the occurrence of serious adverse drug reactions (ADRs), with ceftazidime-avibactam possibly showing a more favourable risk-benefit profile. We investigated the potential impact of resistance on ADR reports in countries with different prevalence of KPC isolates (Italy vs. United Kingdom [UK]), and described safety profile of newer and older antibiotics used in KPC infections. Methods Three spontaneous reporting systems (SRSs) with different features (Italy, UK and worldwide FAERS) were used to describe safety profiles of colistin, meropenem, tigecycline, gentamicin and ceftazidime-avibactam in terms of System Organ Class and Preferred Term level. ADRs were plotted with prevalence of KPC isolates in Italy and UK. A comparison between before-after the KPC outbreak period (1999-2008 vs. 2009-2018) of overall and serious ADRs for selected antibiotics in each SRS was performed. Relationship between total and serious number of ADR reports per year and KPC isolates per year after KPC outbreak (2009-2017) was investigated for both Italy and UK. Results A total of 16,329 ADR reports were collected in the three SRSs, with meropenem (42.6%) and gentamicin (36.9%) having the highest number of reports. Significant increase in total and serious ADR reports after the KPC outbreak compared to previous 10 years was found for colistin, meropenem and gentamicin (p < 0.01). No significant increase in tigecycline ADRs was reported in FAERS and UK database. Unexpected safety signals involving selected antibiotics were not detected. Significant positive relationship between overall and serious ADR reports and KPC isolates per year for both Italy (p < 0.01; p = 0.005) and UK (p = 0.032; p = 0.013) was found. Conclusion KPC outbreak led to significant increase in ADRs to selected antibiotics, and a close relationship with antimicrobial resistance was found, both in countries with high and low resistance rate. New safety signals were not detected for selected agents. Active surveillance should be maintained to promptly identify unexpected safety issues.